Efficacy and safety of fenofibrate as an add-on in patients with elevated triglyceride despite receiving statin treatment. (15th October 2016) - Zhao, Shuiping; Wang, Fang; Dai, Yangyang; Lin, Ling; Tong, Qiguang; Liao, Yuhua; Yin, Yuehui; Wang, Guang; Yan, Yafei; Li, Xiaodong; Wang, Daowen; Wei, Ping; et al.
Abstract: Background: Since the withdrawal of cerivastatin, statin–fibrate combination therapy has been questioned in China due to safety concern. The objective of this study was to evaluate the efficacy and safety profile of fenofibrate as an add-on in patients with dyslipidemia despite receiving statin therapy. Methods: This was a prospective, multi-center, single-arm, open-label study conducted in Chinese dyslipidemia patients with high CV risk. Fenofibrate (200 mg daily) was added to the existing statin treatment for 8 weeks. Lipid profile and safety parameters were measured and compared between baseline and after the treatment. Five hundred and six subjects were enrolled from 28 sites from 14 cities nationwide across China. Results: After 8 weeks of fenofibrate treatment, the mean blood triglyceride level decreased to 1.77 mmol/L (38.1% reduction vs. 3.00 mmol/L at the baseline; p  < 0.01). Mean high-density lipoprotein cholesterol (high density lipoprotein cholesterol) was increased to 1.22 mmol/L (by 17.4% from 1.07 mmol/L at the baseline; p  < 0.01). No case of severe muscle damage (defined as elevated creatine kinase over 5 times of upper limit of normal (ULN) or rhabdomyolysis was observed. Conclusion: In statin-treated patients with high CV risk who had elevated triglyceride, adding fenofibrate could improve lipid profile with acceptable safety profiles.